Práticas participativas de canais multimídia infantis no espaço digital - Cavalcante, João Everton Lima (2024)
This research investigated the use of the digital space by children's multimedia networks in promoting participatory practices with children. To achieve this, we developed a Multiple Case Study (YIN, 2001), in which we analyzed transmedia content (FECHINE et al., 2013) produced by two Latin American networks, Gloob (Brazil) and Eureka (Colombia). The first case analyzed was a set of content produced by the private network Gloob during the Covid-19 pandemic, under the hashtag #GLOOBEMCASA. The second one consisted of analyzing the program Mundo Eureka, co-created and co-produced by the team from the public network Eureka and its group of advisors, composed of children and teenagers. The identification and analysis of participatory practices took into account the three dimensions of media participation classified by Carpentier (2011), Access, Interaction and Participation; and also the levels of child participation listed by Lansdown (2009), classified as consultative processes, collaborative processes and child-led processes. As a result, we identified, in the Access dimension, the presence of free content that makes reference to paid content; the use of digital platforms to distribute content; and the possibility of using mobile devices with low technical capacity to access them. In the Interaction dimension, they presented consultations through posts and polls; interactive games and challenges; and games that can be played both online and offline. In the Participation dimension, we identified the presence of practices of co-creation and co-production of programs; a media education initiative for the production of audiovisual content; and public calls for submissions of works of art created by children through websites. The study revealed, in both cases, the use of transmedia strategies of propagation, in which content reference themselves in social media and digital platforms; and expansion, in which complementary content is produced to the main media, exploring different formats. We also noted that transmedia content has been used as an advertising tool in the attempt to encourage audiences in the desire of consumption related to paid content. Based on the above, the study highlights the importance of activating and reinforcing protection mechanisms regarding personal data and children's exposure on digital platforms, taking into account their rights and well-being in relation to the digital space (LIVINGSTONE, 2016; ONU, 2021).